High prevalence of Pseudomonas aeruginosa carriage in residents of French and German long-term care facilities. (October 2022) - Martak, Daniel; Gbaguidi-Haore, Houssein; Meunier, Alexandre; Valot, Benoit; Conzelmann, Nadine; Eib, Michael; Autenrieth, Ingo B.; Slekovec, Céline; Tacconelli, Evelina; Bertrand, Xavier; Peter, Silke; Hocquet, Didier; et al.
Abstract: Objectives: To determine prevalence, incidence, and factors associated with Pseudomonas aeruginosa (PA) intestinal carriage in residents of long-term care facilities (LTCFs) and to understand the population structure of this pathogen in LTCFs from two European countries. Methods: We assessed the prevalence of PA intestinal carriage and the incidence of acquisition by collecting fecal samples from 403 residents of 20 LTCFs. We collected 289 environmental samples from sinks and drinking water. Factors associated with carriage and acquisition of intestinal PA were identified. All PA isolates had their antibiotic phenotypic resistance profile determined and their genome sequenced, from which we assessed the population structure of the collection and identified resistance determinants. Results: We found a high proportion of residents with PA intestinal carriage (51.6%) over the entire study period. Over the follow-up period, 28.6% of the residents acquired intestinal PA. Older age (OR, 1.29; 95% CI, 1.09–1.52; p = 0.002), urinary incontinence (OR, 2.56; 95% CI, 1.37–4.88; p = 0.003), and male sex (OR, 2.55; 95% CI, 1.05–6.18; p = 0.039) were associated with higher probability of carriage. Wheelchair usage (OR, 4.56; 95% CI, 1.38–15.05; p = 0.013) and a body mass index >25 (OR, 3.71; 95% CI, 1.17–11.82; p = 0.026) were associated with higher risk of PA acquisition. Population structure of our isolates was mainly non-clonal with 112 different STs among the 241 isolates. Most represented STs were high risk clones ST253 ( n  = 26), ST17 ( n  = 11), ST244 ( n  = 11), ST309 ( n  = 10), and ST395 ( n  = 10). Most PA isolates (86.3%) were susceptible to antibiotics, with no acquired genes conferring resistance to antipseudomonal agents. Discussion: We found an unexpected high prevalence of PA intestinal carriage in LTCF residents mainly associated with individual-level factors. Our study revealed a polyclonal PA population structure suggesting that individual acquisition is more frequent than resident-to-resident transmission.